DOI: 10.29007/6z3k
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Teaching and Learning Experience by Online Course Diary Tool: Qualitative Exploration of Teachers’ Perspective

Abstract: Due to the rapid shift to online learning, it has become increasingly difficult for teachers to monitor students’ learning experiences. This paper analyzes teachers’ experiences with an online tool for monitoring students’ metacognitive states during the learning process. Through an open-ended questionnaire, we collected teachers’ aims for starting to use the tool and experienced benefits. Our results show that teachers use this tool to understand the learning status of students in greater depth and to adjust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Earlier empirical studies have demonstrated a close relationship between the self-reported use of metacognitive strategies like monitoring and more sophisticated epistemic cognition (Bromme et al, 2010b). The SLD offers several means for monitoring strategies, e.g., monitoring one's competence on topics, perceived difficulty, and experienced emotions (Kivimäki et al, 2019;Kivimaki et al, 2021). We found that MS students differ from AJ and DS student profiles in their diary use.…”
Section: Hypothesis 3: Patterns In Justification Use Relate To Diary Usementioning
confidence: 65%
“…Earlier empirical studies have demonstrated a close relationship between the self-reported use of metacognitive strategies like monitoring and more sophisticated epistemic cognition (Bromme et al, 2010b). The SLD offers several means for monitoring strategies, e.g., monitoring one's competence on topics, perceived difficulty, and experienced emotions (Kivimäki et al, 2019;Kivimaki et al, 2021). We found that MS students differ from AJ and DS student profiles in their diary use.…”
Section: Hypothesis 3: Patterns In Justification Use Relate To Diary Usementioning
confidence: 65%